Nano/microvehicles for efficient delivery and (bio)sensing at the cellular level. Issue 10 (4th September 2017) - Campuzano, S.; Esteban-Fernández de Ávila, B.; Yáñez-Sedeño, P.; Pingarrón, J. M.; Wang, J.
Abstract : A perspective review of recent strategies involving the use of nano/microvehicles to address the key challenges associated with delivery and (bio)sensing at the cellular level is presented. Abstract : A perspective review of recent strategies involving the use of nano/microvehicles to address the key challenges associated with delivery and (bio)sensing at the cellular level is presented. The main types and characteristics of the different nano/microvehicles used for these cellular applications are discussed, including fabrication pathways, propulsion (catalytic, magnetic, acoustic or biological) and navigation strategies, and relevant parameters affecting their propulsion performance and sensing and delivery capabilities. Thereafter, selected applications are critically discussed. An emphasis is made on enhancing the extra- and intra-cellular biosensing capabilities, fast cell internalization, rapid inter- or intra-cellular movement, efficient payload delivery and targeted on-demand controlled release in order to greatly improve the monitoring and modulation of cellular processes. A critical discussion of selected breakthrough applications illustrates how these smart multifunctional nano/microdevices operate as nano/microcarriers and sensors at the intra- and extra-cellular levels. These advances allow both the real-time biosensing of relevant targets and processes even at a single cell level, and the delivery of different cargoes (drugs, functional proteins, oligonucleotides and cells) for therapeutics, gene silencing/transfection and assisted fertilization, while overcoming challenges faced by current affinity biosensors and delivery vehicles. Key challenges for the future and the envisioned opportunities and future perspectives of this remarkably exciting field are discussed.